Islamic architecture in Iran : poststructural theory and the architectural history of Iranian Mosques - Khaghani, Saeid (London ; New York : I.B. Tauris ; New York : Distributed in the United States and Canada exclusively by Palgrave Macmillan, 2012)
'The architecture of the Islamic world is predominantly considered in terms of a dual division between'tradition' and'modernity' - a division which, Saeid Khaghani here argues, has shaped and limited the narrative applied to this architecture. Khaghani introduces and reconsiders the mosques of eighth- to fifteenth-century Iran in terms of poststructural theory and developments in historiography in order to develop a brand new dialectical framework. Using the examples of mosques such as the Friday Mosques in Isfahan and Yazd as well as the Imam mosque in Isfahan, Khaghani presents a new way of thinking about and discussing Islamic architecture, making this valuable reading for all interested in the study of the art, architecture, and material culture of the Islamic world.'--Publisher.
Introduction -- Islam as an Attribution -- Iranism -- The Mosque as Public Space -- Difference and the Iranian Architectural Discourse -- Difference and Particularity -- Conclusion.
Keywords: Islamic architecture -- Iran -- History; Mosques -- Iran -- History -- To 1500.